(untitled) (International Journal of Engineering Research, 2025)
The rapid expansion of the global economy has led to an increased focus on energy reserve strategies and production necessities within the petrochemical industry. As a result, the scale of petrochemical storage tank farms has expanded significantly, leading to increased capacity and more intensive development efforts. In recent years, several severe incidents—such as oil spills, explosions, and fires linked to storage tanks—have underscored the urgent need for a comprehensive investigation into the combustion and explosion dynamics of these facilities. This paper examines the mechanisms of explosive combustion in environments involving crude oil tanks, offering an extensive review of both domestic and international research advancements in the areas of crude oil explosions and combustion. Furthermore, it discusses several widely recognized risk assessment methodologies relevant to managing storage tank risks. Both qualitative and quantitative evaluations, complemented by simulations of accident consequences, can provide vital technical support for safety management and emergency response initiatives. To mitigate the risk of future incidents, it is crucial to draw lessons from previous accidents, enhance theoretical research, and implement effective safety protocols. This strategy will not only improve the safety of national energy reserves but also promote the overall integrity of the petrochemical industry